Method of KVM virtual machine live migration in cross-platform based on Cloudstack and OpenStack - Nan ZHENG; Li-nan CHEN; Li-xiong ZHENG; Yan MA (Tongxin xuebao)
To make KVM virtual machine which have been created in CloudStack platform identified and taken over correctly in CloudStack and OpenStack concomitant environment,propose a method for live migration of KVM virtual machine from CloudStack to OpenStack.By combining traditional KVM virtual machine migration method based on local storage and the characteristics of CloudStack and OpenStack cloud computing platform,regrouping virtual machine migration-related documents,we achieved the dynamic migration of virtual machines across platforms.The experimental results show that the method can not only successfully completed the KVM virtual machine migration task from CloudStack to OpenStack,but also have no more other time cost than the traditional method.